Can Sci-Tech Finance Pilot Policies Reduce Carbon Emissions? Evidence From 252 Cities in China - Lu, Ying; Guo, Jingxian; Ahmad, Mahmood; Zhang, Haotian (Frontiers in Environmental Science, 2022)
It is widely believed that science and technology (sci-tech) finance can pave the way to combat environmental degradation by promoting innovation in environment-related technologies. However, limited research is available to support this argument, and literature is silent on how sci- Sci-tech Finance Pilot Policies influence the carbon emissions in China. Therefore, this study investigates the impact of technology and financial integration pilot policy (TFIP) on carbon emissions and its dynamic effects, heterogeneity, and mechanisms in 252 cities in China. To do this, yearly data from 2006 to 2019 is employed using the PSM-DID (Propensity Score Matching-Difference in Difference) method. The results unveiled that: (1) TFIP can effectively reduce the scale and intensity of carbon emissions in pilot cities. The TFIP shows a U-shaped distribution with CO2_Size and CO2_intensity, which reach the low point in the fifth year. TFIP has a lagging effect on carbon emissions, which significantly reduces carbon emissions in the second year. The robustness test verifies our conclusion. (2) The heterogeneity test results show that the effect of TFIP is heterogeneous depending on the spatial and city attributes. TFIP can effectively reduce carbon emissions in the eastern region and resource-based cities. However, in the central, western, and non-resource-based cities, the reduction effect of TFIP is not obvious. (3) The impact mechanism finds that TFIP reduces the scale of carbon emissions by enhancing the green innovation capacity and rationalizing the production structure in the pilot cities. Several policy recommendations are proposed based on the findings including vigorous development of sci-tech finance to achieve sustainable development of the economy.